Quality of life and social support among persons with nasopharyngeal cancer receiving combined therapy - Che Abdullah, Che Azunie; Sukonthasarn, Achara; Somrarynyart, Mayulee (2016)
Introduction: The quality of life of persons with nasopharyngeal cancer (NPC) receiving combined therapy is an important point of investigation since the disease and its treatments have an impact on many aspects of life: physical, psychological, social relationships, and environmental aspects. Social support may contribute to a better quality of life for NPC persons. Objectives: The purpose of this study is to examine the level of quality of life and social support among NPC persons receiving combined therapy as well as the relationship between these two variables. Methods: This descriptive correlational study used purposive sampling recruited with 70 subjects from outpatient departments of Kuala Lumpur General Hospital and Penang General Hospital in Malaysia. Instruments used included a demographic data form, the World Health Organization Quality of Life-BREF Malay Version and the Personal Resources Questionnaire 2000 Malay Version. Data were analyzed using descriptive statistic and correlations.